The Association Between Complementary and Alternative Medicine and Health Status Following Acute Myocardial Infarction. Issue 8 (31st May 2016) - Shafiq, Ali; Jayaram, Natalie; Gosch, Kensey L.; Spertus, John A.; Buchanan, Donna M.; Decker, Carole; Kosiborod, Mikhail; Arnold, Suzanne V.
ABSTRACT: Background: Complementary and alternative medicines (CAM) are commonly used in patients with cardiovascular disease. Although there is lack of evidence regarding the benefit of CAM on cardiovascular morbidity and mortality, health‐status benefits could justify CAM use. Hypothesis: Adoption of mind‐body CAM after acute myocardial infarction (AMI) is associated with improved health status, though other forms of CAM are not associated with health‐status improvement. Methods: Patients with AMI from 24 US sites were assessed for CAM use (categorized as mind‐body, biological, and manipulative therapies) prior to and 1 year after AMI. Among patients who reported not using CAM prior to their AMI, association of initiating CAM on patients' health status at 1 year after AMI was assessed using Angina Frequency and Quality of Life domains from the Seattle Angina Questionnaire and the Short Form‐12 Physical and Mental Component scales. Multivariable regression helped examine association between use of different CAM therapies and health status. Results: Among 1884 patients not using CAM at the time of their AMI, 33% reported initiating ≥1 forms of CAM therapy 1 year following AMI: 62% adopted mind‐body therapies, 42% adopted biological therapies, and 15% began using manipulative therapies. In both unadjusted and adjusted analyses, we found no association between different types of CAM use and health‐status improvement after AMI. Conclusions: There was no association between CAM use and health‐status recovery after AMI. Until randomized trials suggest otherwise, these findings underscore the importance of focusing on therapies with proven effectiveness after AMI.